Hematological Disorders in patients with Connective Tissue Diseases - Naveed Aslam Lashari, Zia Ul Haq, Sumreen, Nadeem Sharif, Khushbakht Shafqat, Zahida Shaikh, Laraib Moeed (Pakistan Journal of Medical & Health Sciences, 2024)
Background: This study describes connective tissue diseases, including systemic lupus erythematous, Sjögren’s syndrome, systemic sclerosis, mixed connective tissue disease and overlap syndrome, and their associations with hematologic disorders. Consequently, anemia, leukopenia, thrombocytopenia, and antiphospholipid antibody (APLA) are included as morbidity indicators and can be used to determine further treatment strategies for this disease. Methods: Therefore, a cross-sectional study was performed for six months from August 2024 to January 2025 at PAF Hospital Islamabad. Two hundred consecutive patients met the classification criteria for CTDs, including 50% SLE, 20% SSc, 15% Sjögren syndrome, 10% overlap syndrome, and 5% MCTD. The data gathered from the files consisted of demographic data, complete blood count (CBC) data, autoantibody profiles and clinical data. According to the ISTH, hematologic disorders were diagnosed, whereas APLA testing was performed via ELISA and coagulation tests. The descriptive statistical tests were computed through the Statistical Package of the Social Sciences (SPSS) software version 26.0 and the level of significance was considered to be 0.05. Results: We reported that 78% of the patients had at least one altered hematologic parameter. Approximately 52% of the study subjects were found with anemia, 33% with leukopenia, 32.5% had lymphopenia, and 15% had thrombocytopenia, whereas pancytopenia was found in only 6.5% of the patients. With respect to hematologic changes, SLE patients manifested the greatest percentage of anemia at 70%, leukopenia at 40% and thrombocytopenia at 20%. Therefore, 33.5% of the patients were positive for APLA, and 10% of the total group fulfilled the criteria for secondary APS. Conclusion: Cryptogenic hematology is common in patients with CTDs and more common in patients with SLE and MCTD. Therefore, it is crucial in CTD that blood counts should be researched on a regular basis together with APLA antibodies because their shifts indicate some issues. Keywords: Systemic lupus erythematosis, systemic sclerosis, sjogrens syndrome, mixed connective tissue disorders and antiphospholipid antibody syndrome.